Microstructural Changes in Co Films Depending on MOCVD Conditions; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Hairullin (Khayrullin) R. R. Rustam Ravilievich (Chemistry and Physics of Materials, Environmental Materials, 2015)
Title screen